1967
DOI: 10.3181/00379727-125-32140
|View full text |Cite
|
Sign up to set email alerts
|

Production of Anti-Mycoplasma (PPLO) Antibodies in Rabbits.

Abstract: G-200 columns when either propionic acid or formic acid was used for elution. The phenograms obtained from column-separated polypeptide chains were compared, and no difference was found in either the L chain or H chain banding patterns of yG-globulin from bursectomized and normal chickens. These results indicate that the subunit of yG-globulin is the same for bursectomized and normal chickens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1973
1973
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…All strains in Antiserum production. New Zealand rabbits were vaccinated by the method of Morton, and Roberts (1967), 3 ml of antigen in adjuvant being given by injection into the muscle, dermis and footpad, followed 3 weeks later by 2 ml intramuscularly. The growth-inhibiting titres obtained by this technique alone were unsatisfactory however, and two supplementary i.v.…”
mentioning
confidence: 99%
“…All strains in Antiserum production. New Zealand rabbits were vaccinated by the method of Morton, and Roberts (1967), 3 ml of antigen in adjuvant being given by injection into the muscle, dermis and footpad, followed 3 weeks later by 2 ml intramuscularly. The growth-inhibiting titres obtained by this technique alone were unsatisfactory however, and two supplementary i.v.…”
mentioning
confidence: 99%
“…The use of adjuvants has long been advocated for the production of high-titred mycoplasma antisera (Morton & Roberts, 1967) but some species of mycoplasma consistently fail to produce certain types of anti-mycoplasma antibodies in rabbits (Carroll, Rollins & Jasper, 1976) even when an adjuvant is used. The results presented reveal that for M. bovis the use of an adjuvant is desirable for production of specific precipitins in the GP and GD tests, but it was also shown that a number of anti-medium precipitins were produced which cross-reacted with M. bovigenitalium antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Antisera against Anaeroplasma strains 6-1, 7LA, JR, and 161 were prepared in rabbits. The inoculation procedure was similar to that described by Morton and Roberts (8). The sites of inoculation, amounts of inoculum, and intervals between inoculations are indicated in Table 2.…”
Section: Methodsmentioning
confidence: 99%